2006
DOI: 10.1373/clinchem.2006.066845
|View full text |Cite
|
Sign up to set email alerts
|

High Lipoprotein-Associated Phospholipase A2 Is a Risk Factor for Recurrent Coronary Events in Postinfarction Patients

Abstract: Background: Recent studies demonstrate that lipoprotein-associated phospholipase A 2 (Lp-PLA 2 ) is a risk factor for cardiovascular disease presumably deriving from generation of proinflammatory and proatherogenic species through its hydrolytic activity on lipoprotein-associated phospholipids. The goal of this study was to assess the relationship of Lp-PLA 2 with a set of thrombogenic, lipid, inflammatory, and metabolic blood markers and to determine whether plasma Lp-PLA 2 is a risk factor for recurrent coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 23 publications
3
55
0
5
Order By: Relevance
“…Prior to the current study, several lines of evidence supported Lp‐PLA 2 activity as a risk indicator of adverse outcomes both in patients with stable CHD and in the general population in addition to being potentially involved in the development of atherosclerosis and vulnerable plaque at the tissue level 6, 7, 8, 9, 22, 23, 24, 25, 26, 27. Furthermore, in 2 case–control studies, natural deficiency of Lp‐PLA 2 activity due to carriage of the V279F‐null allele in the Lp‐PLA 2 gene was associated with a lower risk of developing CHD 30.…”
Section: Discussionmentioning
confidence: 73%
“…Prior to the current study, several lines of evidence supported Lp‐PLA 2 activity as a risk indicator of adverse outcomes both in patients with stable CHD and in the general population in addition to being potentially involved in the development of atherosclerosis and vulnerable plaque at the tissue level 6, 7, 8, 9, 22, 23, 24, 25, 26, 27. Furthermore, in 2 case–control studies, natural deficiency of Lp‐PLA 2 activity due to carriage of the V279F‐null allele in the Lp‐PLA 2 gene was associated with a lower risk of developing CHD 30.…”
Section: Discussionmentioning
confidence: 73%
“…For the diabetic study group, there were a total of 199 patients, with 173 having complete serum biomarker levels and 145 with complete biomarker levels as well as T145M genotyping. Reference populations comprised nondiabetic patients of the THROMBO study (12). Details of the entire THROMBO study population have been reported previously (13), and, as noted, the study was carried out with approval of and according to guidelines of the research subjects review boards.…”
Section: Methodsmentioning
confidence: 99%
“…The prognostic value of Lp-PLA 2 for cardiovascular events has also been demonstrated in patients with stable CAD. [91][92][93] In addition to predicting the risk of a cardiac event, Lp-PLA 2 has been suggested as a risk predictor for restenosis. In a recent study involving 326 patients eligible for stent placement, elevated baseline levels of Lp-PLA 2 (200 ng/mL) were associated with an increased risk for restenosis after 1 year.…”
Section: Lp-plamentioning
confidence: 99%